Fidelity to and comparative results across behavioral interventions evaluated through the RE-AIM framework: a systematic review. Issue 1 (December 2015) - Harden, Samantha; Gaglio, Bridget; Shoup, Jo; Kinney, Kimberlee; Johnson, Sallie; Brito, Fabiana; Blackman, Kacie; Zoellner, Jamie; Hill, Jennie; Almeida, Fabio; Glasgow, Russell; Estabrooks, Paul
Abstract Background The reach, effectiveness, adoption, implementation, and maintenance (RE-AIM) framework was developed to determine potential public health impact of interventions (i.e., programs, policy, and practice). The purpose of this systematic review was to determine (1) comparative results across accurately reported RE-AIM indicators, (2) relevant information when there remains under-reporting or misclassification of data across each dimension, (3) the degree to which authors intervened to improve outcomes related to each dimension, and (4) the number of articles reporting RE-AIM dimensions for a given study. Methods In April 2013, a systematic search of the RE-AIM framework was completed in PubMed, PSYCHInfo, EbscoHost, Web of Science, and Scopus. Evidence was analyzed until January 2015. Results Eighty-two interventions that included empirical data related to at least one of the RE-AIM dimensions were included in the review. Across these interventions, they reached a median sample size of 320 participants (M  = 4894 ± 28, 256). Summarizing the effectiveness indicators, we found that: the average participation rate was 45 % (±28 %), 89 % of the interventions reported positive changes in the primary outcome and 11 interventions reported broader outcomes (e.g., quality of life). As for individual-level maintenance, 11 % of studies showed effects ≥6 months post-program. Average setting and staff adoption rates were 75 % (±32 %) and 79 % (±28 %), respectively. Interventions reported being delivered as intended (82 % (±16 %)) and 22 % intervention reported adaptations to delivery. There were insufficient data to determine average maintenance at the organizational level. Data on costs associated with each dimension were infrequent and disparate: four studies reported costs of recruitment, two reported intervention costs per participant, and two reported adoption costs. Conclusions The RE-AIM framework has been employed in a variety of populations and settings for the planning, delivery, and evaluation of behavioral interventions. This review highlights inconsistencies in the degree to which authors reported each dimension in its entirety as well as inaccuracies in reporting indicators within each dimension. Further, there are few interventions that aim to improve outcomes related to reach, adoption, implementation, and maintenance.